Wade and the scorpion's claw - Abbott, Tony, 1952-; Perkins, Bill (Illustrator) (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2014)
"In this first in a series of ... [companion] novellas [to] the Copernicus legacy series, Wade travels to Hawaii and San Francisco in a race to find one of the twelve ancient relics"--
Includes an excerpt from the next book in the Copernicus legacy series.
Keywords: Adventure stories; Voyages and travels -- Juvenile fiction; Antiquities -- Juvenile fiction; Secret societies -- Juvenile fiction; Adventure and adventurers -- Fiction; Voyages and travels -- Fiction; Antiquities -- Fiction; Secret societies -- Fiction; Adventure fiction